Fundamental resolution limit of quantum imaging with undetected photons - Vega, Andres; Santos, Elkin A.; Fuenzalida, Jorge; Basset, Marta Gilaberte; Pertsch, Thomas; Graefe, Markus; Saravi, Sina; Setzpfandt, Frank (Physical Review Research, 2022)
Quantum imaging with undetected photons relies on the principle of induced coherence without induced emission and uses two sources of photon pairs with a signal- and an idler photon. Each pair shares strong quantum correlations in both position and momentum, which allows us to image an object illuminated with idler photons by just measuring signal photons that never interact with the object. In this work, we theoretically investigate the transverse resolution of this nonlocal imaging scheme through a general formalism that treats propagating photons beyond the commonly used paraxial approximation. We hereby prove that the resolution of quantum imaging with undetected photons is fundamentally diffraction limited to the longer wavelength of the signal and idler pairs. Moreover, we conclude that this result is also valid for other nonlocal two-photon imaging schemes.
CRIS-Team Scopus Importer:2023-04-20